Urban Domestic: Water Resources as the Basis of Everyday Life in Urban Kampong Sekayu Semarang - Timur, Veronica Kinanthi Cogan; Harani, Arnis Rochma; Riskiyanto, Resza (Sinektika: Jurnal Arsitektur, 2026)
This paper explores limited spatial conditions and access to water influence domestic arrangements in low-income urban kampong houses. It investigates water related needs to drive creative spatial strategies, including the appropriation of front house areas, shared courtyards, and semi public spaces that associate domestic service areas with the rear sections of dwellings. Water resources play a fundamental role in shaping domestic life and spatial practices in urban kampong environments. In Kampong Sekayu, Semarang, water is not only a vital element for everyday domestic service activities such as cooking, washing, and bathing but also a core determinant in the spatial organization of dwellings. The study also considers the impact of communal water use and neighborhood social structures on household spatial adaptations. By exploring how space is organized through the perspective of water-dependent household activities, this study highlights the unique spatial and social characteristics of urban kampong life, where water becomes a major organizing force in the everyday household landscape.